Experimental Verification of Three phase quasi Switched Boost Inverter with an Improved PWM Control - Sriramalakshmi Palanidoss; Sreedevi V.T. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
In this paper, an experimental investigation of a three phase quasi Switched Boost Inverter (qSBI) topology is proposed and analysed with an improved Pulse Width Modulation strategy. The qSBI is capable of providing both boost and inversion actions in a single stage. The improved PWM control technique can provide a higher boost with the reduced duty ratio. The theoretical analysis presented in this work is validated using an experimental set up of 100W qSBI topology and hardware results are shown for verification. The improved PWM strategy is implemented and firing pulses are generated in FPGA SPARTAN 3E kit. With the duty ratio of 0.05, the peak ac load voltage of 80 V is obtained. The performance of three phase qSBI is analysed with both conventional PWM strategy and improved PWM strategy. The observations are presentated in detail.